Literasi Keuangan Syariah lewat Podcast Dakwah dan Digitalisasi Majelis Taklim Sorong - Kahinah, Dwi Iin; Masseni, Masseni; Rokhimah, Rokhimah; Karfin, Karfin; Hasrun, Andi; Amanda, Nila (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Enhancing Islamic financial literacy and utilizing digital financial systems are crucial, particularly for women in the Al-Muhajirin Majelis Taklim community in Sorong City. This group often faces challenges in financial management, highlighting the need for greater understanding of sharia-compliant financial principles. This community service program aims to provide education through lectures, reinforcement by lecturers, and interactive discussions. An innovative approach through interactive Islamic preaching podcasts was also used to present material in a more engaging and relevant manner. The program has demonstrated improvements in participants’ understanding and skills in managing finances according to Islamic principles, as well as in safely using digital financial technology. The success of the activity is evident from the high level of community participation, strengthening Islamic financial literacy among majelis taklim members. It is expected that this program will serve as a sustainable model for empowering sharia-based financial literacy.